Intradural conus and cauda equina tumours: a retrospective review of presentation, diagnosis and early outcome. Issue 1 (January 1993) - Mathew, P; Todd, N V
Abstract : This is a retrospective review of the clinical presentation, diagnosis and management of 62 patients with histologically proven intradural conus and cauda equina tumours. In the majority of cases the clinical presentation clearly suggests the need for further investigation. One fifth of the patients had small intramedullary tumours, which presented particular diagnostic difficulty and required sophisticated cross sectional imaging.